The Decision to (Re)Exist: Histories and Organizational Dynamics within a Quilombola Community in Minas Gerais, Brazil - Marquezini, Hellen; de Vasconcelos Machado Guimaraes, Ludmila; de Oliveira Barreto, Raquel (Organizações & Sociedade, 2024)
This study aims to delve into the mechanisms by which the establishment of ethnic-racial identity safeguards the continuity of a Quilombola Remnant Community (CRQ). Employing psychosociology as its theoretical underpinning and adopting a collective life history methodological approach, this research was conducted within a CRQ situated in the metropolitan region of Belo Horizonte, Minas Gerais, Brazil. Findings underscore the quilombo’s foundational structure, rooted in an ethnicracial identity that galvanizes the elements of resistance, belonging, and lineage, all of which are pivotal for both the individuals and the quilombo’s continued existence. Identity formation emanates from the acknowledgment of ancestry, as individuals align themselves with their historical lineage, recognizing these forebears as integral to their own composition. Such identities foster a sense of belonging within quilombola subjects, thereby perpetuating the group’s (re)existence through a reappropriation of ancestral resistance. Resistance is intrinsic to identity because, prior to the decision of the quilombola subject to exist, resistance is imperative, given that external forces wish to undermine their existence. These markers not only underscore the resilience of the Arturos Quilombola Community (the CRQ under study) in sustaining life and rallying its constituents but also highlight its proactive stance in instituting organizational structures and adaptations in the face of the prevailing status quo.